The Halogen Bond in Weakly Bonded Complexes and the Consequences for Aromaticity and Spin-Orbit Coupling - Ana V. Cunha; Remco W. A. Havenith; Jari van Gog; Freija De Vleeschouwer; Frank De Proft; Wouter Herrebout (Molecules, 2023)
The halogen bond complexes CF<semantics>3</semantics>X⋯Y and C<semantics>2</semantics>F<semantics>3</semantics>X⋯Y, with Y = furan, thiophene, selenophene and X = Cl, Br, I, have been studied by using DFT and CCSD(T) in order to understand which factors govern the interaction between the halogen atom X and the aromatic ring. We found that PBE0-dDsC/QZ4P gives an adequate description of the interaction energies in these complexes, compared to CCSD(T) and experimental results. The interaction between the halogen atom X and the <semantics>π</semantics>-bonds in perpendicular orientation is stronger than the interaction with the in-plane lone pairs of the heteroatom of the aromatic cycle. The strength of the interaction follows the trend Cl < Br < I; the chalcogenide in the aromatic ring nor the hybridization of the C–X bond play a decisive role. The energy decomposition analysis shows that the interaction energy is dominated by all three contributions, viz., the electrostatic, orbital, and dispersion interactions: not one factor dominates the interaction energy. The aromaticity of the ring is undisturbed upon halogen bond formation: the <semantics>π</semantics>-ring current remains equally strong and diatropic in the complex as it is for the free aromatic ring. However, the spin-orbit coupling between the singlet and triplet <semantics>π→π*</semantics> states is increased upon halogen bond formation and a faster intersystem crossing between these states is therefore expected.